2017
DOI: 10.1016/j.jdent.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Polyols and remineralisation of enamel subsurface lesions

Abstract: This controlled in vitro study showed that polyols at physiologically relevant concentrations did not promote remineralisation of enamel subsurface lesions by facilitating calcium uptake into the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The evidence regarding whether xylitol promotes remineralization is equivocal. In 2 in vitro studies, one study result supports the remineralization capability of xylitol [Cardoso et al, 2014] while the other does not [Shen et al, 2017]. In the former study, the remineralization was observed in conjunction with fluoride plus xylitol.…”
Section: Discussionmentioning
confidence: 86%
“…The evidence regarding whether xylitol promotes remineralization is equivocal. In 2 in vitro studies, one study result supports the remineralization capability of xylitol [Cardoso et al, 2014] while the other does not [Shen et al, 2017]. In the former study, the remineralization was observed in conjunction with fluoride plus xylitol.…”
Section: Discussionmentioning
confidence: 86%
“…The experimental varnishes may favor remineralization in deeper layers, either by decreasing the acidogenic potential of plaque or by facilitating the movement of Ca 2+ ions from the saliva towards enamel. 6,11,28 The cross-sectional hardness and integrated area under the curve (calculated by the trapezoidal rule) were calculated to show the integrated loss of subsurface hardness (ΔKHN) 25 for both arms of this study and transverse microradiography was also evaluated for the in situ arm. Ideally, both methods, hardness and transverse microradiography, should be combined, as hardness does not necessarily measure the mineral content and some studies regarding the conversion of hardness to mineral volume are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The teeth were sterilised by storage for at least 14 days in 10% ( v / v ) neutral buffered formalin solution at room temperature. Enamel slabs were cut from the sterilised teeth and subsurface lesions were created as previously described [ 29 ]. This involved painting the enamel slabs with acid-resistant nail varnish (Red 745, Revlon, Oxford, NC, USA) to expose two windows (1 × 7 mm) of enamel on each slab that were demineralised for four days at 37 °C using a demineralisation buffer to produce subsurface lesions of approximately 100 μm depth [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Enamel slabs were cut from the sterilised teeth and subsurface lesions were created as previously described [ 29 ]. This involved painting the enamel slabs with acid-resistant nail varnish (Red 745, Revlon, Oxford, NC, USA) to expose two windows (1 × 7 mm) of enamel on each slab that were demineralised for four days at 37 °C using a demineralisation buffer to produce subsurface lesions of approximately 100 μm depth [ 29 ]. The composition of the demineralisation buffer was 80 mL/L Goodrite K-702 polyacrylate (Lubrizol Advanced Materials Inc., Cleveland OH, USA), 500 mg/L hydroxyapatite (Bio-Gel HTP, Bio-Rad Laboratories, Hercules, CA, USA), and 0.1 M lactic acid (Ajax Chemical, Mt Pritchard, NSW, Australia), adjusted to pH 4.8.…”
Section: Methodsmentioning
confidence: 99%